2002
DOI: 10.1614/0043-1745(2002)050[0721:itmogr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the mechanism of glyphosate resistance in rigid ryegrass (Lolium ridigum)

Abstract: Glyphosate is a broad-spectrum herbicide that has been used extensively for more than 20 yr. The first glyphosate-resistant weed biotype appeared in 1996; it involved a rigid ryegrass population from Australia that exhibited an LD50 value approximately 10-fold higher than that of sensitive biotypes. We have characterized gene expression levels and glyphosate sensitivity of 5-enolpyruvylshikimate 3-phosphate synthase (EPSPS), the target enzyme for glyphosate inhibition, in sensitive and resistant lines derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
69
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 32 publications
9
69
0
3
Order By: Relevance
“…The authors also reported that in this type of resistance, the EPSPS enzyme remains sensitive to glyphosate; what changes is that the amount of herbicide required to reduce the activity of EPSPs increases with the number of copies of gene EPSPs. Baerson et al (2002) found evidence of gene amplification or cosegregation of the specific gene of the varying enzyme in the resistant biotype of Lolium multiflorum.…”
Section: Resultsmentioning
confidence: 94%
“…The authors also reported that in this type of resistance, the EPSPS enzyme remains sensitive to glyphosate; what changes is that the amount of herbicide required to reduce the activity of EPSPs increases with the number of copies of gene EPSPs. Baerson et al (2002) found evidence of gene amplification or cosegregation of the specific gene of the varying enzyme in the resistant biotype of Lolium multiflorum.…”
Section: Resultsmentioning
confidence: 94%
“…There is evidence for enhanced EPSPS expression in glyphosate-resistant weeds, but no previous evidence for EPSPS gene amplification. Two-to threefold elevated EPSPS expression and enzyme activity were found in glyphosate-resistant L. rigidum, and EPSPS from glyphosate-resistant and -susceptible plants were equally sensitive to glyphosate (31). However, the elevated expression was not due to gene amplification because EPSPS gene copy number in L. rigidum was examined using DNA blot hybridizations and glyphosate-resistant lines did not have increased EPSPS gene copy number in comparison with glyphosate-susceptible lines.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have shown that the substitution of proline to serine, leucine, or threonine resulted in more glyphosate resistance in L. rigidum and L. multiflorum (Baerson et al, 2002a;Perez-Jones et al, 2007). Similarly, the presence of two EPSPS loci in susceptible A. palmeri was observed, with one being amplified in glyphosate-resistant plants (Gaines et al, 2013).…”
Section: Epsps Alleles and Amino Acid Substitutions In D Insularis Rmentioning
confidence: 71%